Taking A Stand: Consumer Perceptions Of Brand Activism And Its Impact On Brand Loyalty Among Gen Z And Millennials - Qutratu Aina Wasyifa (UNIVED Press, 2026)
Brand activism has become a significant strategy for companies seeking to engage socially conscious consumers, particularly among Generation Z and Millennials. This study investigates how consumers’ perceptions of brand activism influence brand loyalty, focusing on the mediating roles of brand attitude and brand trust. Guided by the Elaboration Likelihood Model, the research analyzes the effects of perceived issue novelty, controversy, argument quality, authenticity, and motives on brand evaluation. A quantitative approach was employed, collecting data through an online survey of Indonesian consumers familiar with a brand activism campaign. The analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Results show that perceived argument quality and authenticity significantly influence brand trust, which in turn enhances brand loyalty. The findings suggest that building trust through clear, authentic messaging is key to successful brand activism. This study offers valuable insights for marketers in crafting campaigns that resonate with socially aware audiences and foster long-term consumer relationships.